Polysaccharides from Bamboo Shoot (Leleba oldhami Nakal) Byproducts Alleviate Antibiotic-Associated Diarrhea in Mice through Their Interactions with Gut Microbiota - Chen, Canhui; Guan, Xuefang; Liu, Xiaoyan; Zhuang, Weijing; Xiao, Yiqian; Zheng, Yafeng; Wang, Qi (Foods, 2022)
A water-soluble polysaccharide BSP was extracted from the basal part of bamboo shoot, a main by-product of bamboo shoot processing. BSP is composed of glucose (72.8%), xylose (19.43%) and a small amount of galactose, arabinose, glucuronic acid and mannose. The effects of BSP on mice with antibiotic-associated diarrhea (AAD) were investigated. The mice fed with BSP exhibited significant higher bodyweight gain, lower pH value and higher concentrations of SCFAs in the feces compared with those fed with saline. BSP administration reduced the inflammatory cells in the small intestine and colon in the AAD mice, and Firmicutes/Bacteroidetes ratio in the gut was decreased from 0.56 to 0.19. Moreover, BSP administration affected the composition and diversity of the gut microbiota in the AAD mice, particularly on the improvement of beneficial bacteria such as Bacteroides, Lactobacillus and Lachnospiraceae_NK4A136_group. Our results suggest that the polysaccharides from bamboo shoot by-products could be an attractive natural component for gut health and AAD treatment.